Enhancing Satellite Imagesusing DT-CWT in Discrete and Redundant Wavelet Domain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In general, satellite images suffer fromlow resolution (LR)due to the environmental disturbances such as fog and haze, which will degrade the visual quality of the images. In order to find the location or the persons, someone needs to enhance these satellite images to improve the perceptual quality of images. In this a novel resolution enhancement (RE) approach for satellite images is proposed. The proposed approach employeda dual tree complex wavelet transform (DT-CWT) based fusion algorithm in discrete and redundant wavelet domain to obtain a high resolute (HR) satellite images.Majorly, there are two stages in this algorithm, which includes the enhancement of a LR satellite images by enforcing the concept of both discrete and redundant wavelet (DRW) transforms together. Afterwards, this enhanced HR satellite image is given as a one of the source images to the approach of DT-CWT based image fusion for further enhancement of HR satellite image. Experimental analysis shown that the proposed fusion based satellite image enhancement is performed superior to the conventionalwavelet-based approaches like DWT-RE and DRWT-REin terms of peak signal to noise ratio (PSNR), mean square error (MSE) and structural similarity (SSIM) index.